Straight and angulated abutments in platform switching: influence of loading on bone stress by three-dimensional finite element analysis - Martini, Ana Paula; Freitas Júnior, Amilcar; Almeida, Erika; Rocha, Eduardo Passos [UNESP]; Anchieta, Rodolfo Bruniera; Kina, Sidney; Fasolo, Guilherme Bortolon (Wolters Kluwer, 2012)
PURPOSE: In view of reports in the literature on the benefits achieved with the use of platform switching, described as the use of an implant with a larger diameter than the abutment diameter, the goal being to prevent the (previously) normal bone loss down to the first thread that occurs around most implants, thus enhancing soft tissue aesthetics and stability and the need for implant inclination due to bone anatomy in some cases, the aim of this study was to evaluate bone stress distribution on peri-implant bone, by using three-dimensional finite element analysis to simulate the influence of implants with different abutment angulations (0 and 15 degrees) in platform switching. METHODS: Four mathematical models of an implant-supported central incisor were created with varying abutment angulations: straight abutment (S1 and S2) and angulated abutment at 15 degrees (A1 and A2), submitted to 2 loading conditions (100 N): S1 and A1-oblique loading (45 degrees) and S2 and A2-axial loading, parallel to the long axis of the implant. Maximum (σmax) and minimum (σmin) principal stress values were obtained for cortical and trabecular bone. RESULTS: Models S1 and A1 showed higher σmax in cortical and trabecular bone when compared with S2 and A2. The highest σmax values (in MPa) in the cortical bone were found in S1 (28.5), followed by A1 (25.7), S2 (11.6), and A2 (5.15). For the trabecular bone, the highest σmax values were found in S1 (7.53), followed by A1 (2.87), S2 (2.85), and A2 (1.47). CONCLUSIONS: Implants with straight abutments generated the highest stress values in bone. In addition, this effect was potentiated when the load was applied obliquely.